Massive Fibrin Formation with Consecutive Impairment of Fibrinolysis in Patients with Out-of-Hospital Cardiac Arrest - Gando, Satoshi; Kameue, Takashi; Nanzaki, Satoshi; Nakanishi, Yoshimi (Thrombosis and Haemostasis, 1997)
Hypoxia and ischaemia influence blood coagulation and fibrinolysis. This study has been made to determine whether human cardiopulmonary arrest causes fibrin formation and reduction of fibrinolysis. Serial levels of fibrinopeptide A (FPA), fibrinopeptide Bβ15-42 (FPBβ15-42), D-dimer, tissue plasminogen activator antigen concentration (t-PA antigen), t-PA activity, plasminogen activator inhibitor-1 antigen concentration (PAI-1 antigen), and PAI-1 activity were determined in 63 patients with out-of-hospital cardiopulmonary arrest. In the resuscitated patients, the markedly elevated FPA (194.8 ± 54.2 ng/ml) at the beginning of cardiopulmonary resuscitation (CPR) significantly decreased to 32.4 ± 9.1 ng/ml at 24 h after admission (p <0.01), however, this was still about 20 times that of the normal controls. FPBβ15-42 and D-dimer increased from the start of CPR to 60 min (189.3 ± 97.4 ng/ml; p <0.01 and 7726 ± 3556 ng/ml; p <0.001, respectively), and then decreased at 24 h after arrival at the Emergency Department (40.4 ±11.1 ng/ml and 5434 ± 1049 ng/ml, respectively). At 30 min after arrival, FPA and FPBβ15-42 significantly differed between the resuscitated patients and the patients who died (p <0.001 and P <0.05, respectively). Although t-PA antigen and t-PA activity was elevated at the time of arrival, 24 h thereafter, no t-PA activity was detected. At 24 h after admission, PAI-1 antigen and PAI-1 activity were significantly increased (472.2 ± 145.5 ng/ml; p <0.001 and 103.6 ± 36.1 IU/ml; p <0.001, respectively). In conclusion, during and after CPR in patients with out-of-hospital cardiac arrest, massive fibrin generation with consecutive impairment of fibrinolysis were observed. These fibrin-mediated events may have some role in the derangement of vital organ function after cardiac arrest.